The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1365-3059.2000.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

A general model of plant‐virus disease infection incorporating vector aggregation

Abstract: In plant-virus disease epidemiology, dynamical models have invariably incorporated a bilinear inoculation rate that is directly proportional to both the abundance of healthy (susceptible) hosts and the abundance of infective vectors. Similarly, the acquisition rate is usually assumed to be directly proportional to the abundance of nonviruliferous vectors and that of infectious hosts. These bilinear assumptions have been questioned for certain human diseases, and infection rates that incorporate power parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 48 publications
0
61
0
5
Order By: Relevance
“…Essa época foi precedida por contínua emissão de brotos e folhas novas. Para Zhang et al (2000), folhas e ramos novos são locais favoráveis à alimentação de vetores. A emissão de novos brotos parece atrair não apenas a população do ácaro, como também a população do ácaro virulífero, uma vez que a variável fenológica NBRONOV esteve positivamente associada à INPLSIN, conforme detectado pela regressão Poisson.…”
Section: Discussionunclassified
“…Essa época foi precedida por contínua emissão de brotos e folhas novas. Para Zhang et al (2000), folhas e ramos novos são locais favoráveis à alimentação de vetores. A emissão de novos brotos parece atrair não apenas a população do ácaro, como também a população do ácaro virulífero, uma vez que a variável fenológica NBRONOV esteve positivamente associada à INPLSIN, conforme detectado pela regressão Poisson.…”
Section: Discussionunclassified
“…Epidemiological studies of infectious diseases have shown that the rate of transmission and spread of a contagion are strongly influenced by the spatial aggregation of hosts, the relative proportions of these hosts that are susceptible or immune to infection, and by the rates of movement of infected hosts to uninfected populations (Power 1996;Zhang et al 2000). 'Hub-andspoke' or 'stepping stone' invasions are direct analogues of these models.…”
Section: Implications For the Prevention Of Biological Invasionsmentioning
confidence: 99%
“…An additional factor that can aid invasion and displacement is the acceleration of population increase by the invader through mutualism with begomoviruses McKenzie 2002;Zhang et al 2000;Jiu et al 2007). observed that the B biotype showed greater egg-to-adult survival on pumpkin infected with the watermelon curly mottle strain of Squash leaf curl virus compared with uninfected plants.…”
Section: Whitefly-begomovirus Interactionsmentioning
confidence: 99%
“…observed that the B biotype showed greater egg-to-adult survival on pumpkin infected with the watermelon curly mottle strain of Squash leaf curl virus compared with uninfected plants. Zhang et al (2000) used modeling techniques to investigate increased vector fecundity, as well as vector density for B. tabaci feeding on cassava infected with Cassava mosaic virus, speculating that the interaction between virus and vector accelerated the spread of the vector and therefore the virus. Similarly, the B biotype laid more eggs on tomato plants infected with Tomato mottle virus than they did on uninfected plants (McKenzie 2002).…”
Section: Whitefly-begomovirus Interactionsmentioning
confidence: 99%